2017
DOI: 10.12991/marupj.300913
|View full text |Cite
|
Sign up to set email alerts
|

Tiyoüreler, açiltiyoüreler ve 4-tiyazolidinonların sentezi, karakterizasyonu ve antikanser ve antiviral etkilerinin değerlendirilmesi

Abstract: In this study, thiourea derivatives [1][2][3][4] were synthesized by using 2-amino-4-substituted pyridine compounds and these compounds have been used as the starting materials for synthesis of 2-imino-1,3-thiazolidin-4-one ring [5,6]. Two different procedures for 4-thiazolidinone ring closure and synthesis method were optimized. The synthesized compounds were identified by the help of elemental analysis, IR, 1 H-NMR, 13 C-NMR and mass spectral data while the purities of them were proved with TLC. Synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…As expected, the aromatic carbons of all 4‐TZDs, and the methyl carbons of C2 , C4 , C5 , C6 , C8 , C9 , and C10 had chemical shift values between δ 118.32–158.08 ppm, and δ 14.57–24.00 ppm, respectively [21,32,33] . In the mass spectra (Figures S31–S40) of C1 , C2 , C3 , C4 , C5 , C6 , C7 , C8 , C9 , and C10 compounds obtained by the GC/MS method, the observation of [M+] molecular ion peaks at m/z 363, 377, 397, 377, 391, 411, 397, 377, 411, and 391, respectively, confirmed the proposed structures [34] …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…As expected, the aromatic carbons of all 4‐TZDs, and the methyl carbons of C2 , C4 , C5 , C6 , C8 , C9 , and C10 had chemical shift values between δ 118.32–158.08 ppm, and δ 14.57–24.00 ppm, respectively [21,32,33] . In the mass spectra (Figures S31–S40) of C1 , C2 , C3 , C4 , C5 , C6 , C7 , C8 , C9 , and C10 compounds obtained by the GC/MS method, the observation of [M+] molecular ion peaks at m/z 363, 377, 397, 377, 391, 411, 397, 377, 411, and 391, respectively, confirmed the proposed structures [34] …”
Section: Resultssupporting
confidence: 58%
“…[21,32,33] In the mass spectra (Figures S31-S40) of C1, C2, C3, C4, C5, C6, C7, C8, C9, and C10 compounds obtained by the GC/MS method, the observation of [M +] molecular ion peaks at m/z 363, 377, 397, 377, 391, 411, 397, 377, 411, and 391, respectively, confirmed the proposed structures. [34]…”
Section: Chemistrymentioning
confidence: 99%
“…[22] Due to the ability of acylthioureas to form hydrogen bonds, they interact strongly with the active site. [23] Compounds bearing acylthiourea moiety are known to exhibit a wide range of pharmacological properties such as antibacterial, [24,25] antimycobacterial, [26] antifungal, [27,28] antiviral, [29] anticancer, [30] anti-inflammatory [31] and antioxidant [32] activities. In addition to these pharmacological properties of acylthiourea derivatives, it has been reported that they show antidiabetic activity by acting as α-gly and αamylase inhibitors in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…The thioureas so obtained were cyclized by refluxing with ethyl bromoacetate in the presence of sodium acetate to give the title compounds 160 in good yields. Compound 160a revealed good anticancer activity as determined by the MTT assay with 35.82% inhibition in HeLa cells at a dose of 10 μM while no toxicity was shown against NIH3T3 mouse fibroblast cells at the same dose with a 98.19% survival rate [39].…”
Section: Synthetic Strategies and Biological Activity Profile Of 4‐th...mentioning
confidence: 99%